Management of familial benign chronic pemphigus - Arora H; Bray FN; Cervantes J; Falto Aizpurua LA (Dove Medical Press, 2016)
Harleen Arora, Fleta N Bray, Jessica Cervantes, Leyre A Falto Aizpurua Department of Dermatology and Cutaneous Surgery, University of Miami-Miller School of Medicine, Miami, FL, USA Abstract: Benign familial chronic pemphigus or Hailey–Hailey disease is caused by an autosomal dominant mutation in the ATP2C1 gene leading to suprabasilar acantholysis. The disease most commonly affects intertriginous areas symmetrically. The chronic nature of the disease and multiple recurrences make the disease bothersome for patients and a treatment challenge for physicians. Treatments include topical and/or systemic agents and surgery including laser. This review summarizes the available treatment options. Keywords: familial benign chronic pemphigus, corticosteroids, dermabrasion, Hailey–Hailey disease, laser